An environmental scan of impacts and interventions for women with methamphetamine use in pregnancy and their children. Issue 2 (23rd August 2021) - Ackerman, Melissa; Madampage, Claudia; Epp, Lynette J.; Gartner, Kali; King, Alexandra
Abstract: Background: Indigenous women are overrepresented among people who use (PWU) methamphetamine (MA) due to colonialism and intergenerational trauma. Prenatal methamphetamine exposure (PME) is increasing as the number of PWUMA of childbearing age grows. Yet impacts of MA in pregnancy and effective interventions are not yet well understood. Objective: We conducted an environmental scan of published and grey literature (2010–2020) to determine effects of MA use in pregnancy for mothers and their offspring, effective interventions and implications for Indigenous women. Search strategy: A strategic search of Ovid Medline, Embase, ProQuest—Public Health and CINAHL databases identified academic literature, while Google and ProQuest—Public Health identified grey literature. Selection criteria: Article selection was based on titles, abstracts and keywords. The time frame captured recent MA composition and excluded literature impacted by coronavirus disease 2019. Data collection and analysis: Data extracted from 80 articles identified 463 results related to 210 outcomes, and seven interventions. Analysis focused on six categories: maternal, neonatal/infant, cognitive, behavioral, neurological, and interventions. Main results: Maternal outcomes were more congruent than child outcomes. The most prevalent outcomes were general neonatal/infant outcomes. Conclusion: A lack of Indigenous‐specific research on PME and interventions highlights a need for future research that incorporates relevant historical and sociocultural contexts. Synopsis: An environmental scan of published and grey literature (2010–2020) identified impacts of prenatal methamphetamine exposure for mothers and offspring, and identified promising interventions.